The ideas of jadidism and their place in popular spirituality - Sadullayev Ozod Fayzullayevich. (Open Academia, 2024)
This article explores the impact of reformist movement Jadidism on modern folk spirituality in the late 19th and early 20th centuries. The study explores how Jadidist ideas have been integrated into modern spiritual practices, emphasizing the role of movement in the formation of individual and collective spiritual identities. The analysis is based on historical literature, qualitative data and current spiritual trends. The findings suggest that Jadidism emphasizes education, moral reform and modernization, resonating within modern spiritual practices, contributing to the development of a more inclusive and reflective spiritual landscape
Keywords: Jadidism; popular spirituality; spiritual practices